Effectiveness of Proseal laryngeal mask airway and laryngeal tube suction in elective non-laparoscopic surgeries of up to ninety minutes duration: A prospective, randomized study - Swapnil Verma; S P Sharma (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Proseal laryngeal mask airway (LMA) and laryngeal tube suction (LTS) are both supraglottic devices with an esophageal suction port. In the present prospective, randomized study, the effectiveness of airway seal, hemodynamic variables, ability to pass orogastric tube, and postoperative complications with the two devices were evaluated. Material and Methods: This was a prospective, randomized, single-blind study conducted in a hospital-based setting. Sixty patients (American Society of Anesthesiologists Grade I and II) undergoing elective general surgery were randomly allocated to Group A (Proseal LMA) or Group B (LTS), and airway seal pressure (primary outcome), peak pressure, hemodynamic parameters (blood pressure, pulse rate and pulse oximetry) during and 5 min after insertion, insertion time, ease of insertion, and postoperative complications (sore throat and hoarseness of voice for a period of 24 hours) (secondary outcomes) were noted. The quantitative data was summarized as mean and standard deviation, and analyzed using Student's t-test. All the qualitative data were summarized as proportions and analyzed using Chi-square test. The levels of significance and α-error were kept 95% and 5%, respectively, for all statistical analyses. P ≤ 0.05 was considered significant (S). Results: Proseal LMA had shorter insertion time (16.4 ± 5.6 vs. 20.0 ± 3.9 s), higher seal pressure (27.6 ± 4.6 vs. 24.1 ± 5.6 cm of H2O), lesser peak pressure (16.3 ± 2.3 vs. 18.5 ± 3.9 cm of H2O), higher success rate of orogastric tube passage (86.7 vs. 76.7%), and lesser postoperative sore throat (3.3 vs. 10%). Conclusions: Both Proseal LMA and LTS were acceptable alternatives for airway management in elective surgeries with controlled ventilation, but the quality of ventilation was found to be significantly better with Proseal LMA (in terms of higher seal pressure, lesser peak pressure, lesser insertion time, and lesser complications).